Therapeutic thresholds and mechanisms for primary non-response to infliximab in inflammatory bowel disease. (2nd August 2020) - Buhl, Sine; Dorn-Rasmussen, Maria; Brynskov, Jørn; Ainsworth, Mark A.; Bendtzen, Klaus; Klausen, Pia Helene; Bolstad, Nils; Warren, David J.; Steenholdt, Casper
Abstract: Background: Primary non-response to infliximab (IFX) inherits a poor prognosis in inflammatory bowel disease (IBD). We explored underlying mechanisms and therapeutic thresholds in an effort to provide basis for optimizing therapy. Methods: A prospectively followed cohort of 166 IBD patients having received standard IFX induction therapy (5 mg/kg at weeks 2, 6, and 14) had trough IFX and anti-IFX antibodies (Abs) retrospectively assessed at weeks 2 ( n  = 148) and 6 ( n  = 108). Circulating TNFα was measured in matched primary non-responders ( n  = 29) and responders ( n  = 21) at baseline and weeks 6 and 14. Clinical outcome at week 14 was supported by disease activity scores in half of patients. Results: In all, 18 patients (11%) had primary non-response. Infliximab was consistently lower throughout the induction phase in non-responders as compared to responders (Week 2: IFX median 18.9 μg/mL vs. 23.3, p  < .05. Week 6: 8.4 vs. 17.0, p  < .05). Optimal IFX thresholds associated with response was 22.9 μg/mL at week 2 (sensitivity 51%, specificity 80%, AUCROC 0.67, p  < .05) and 11.8 at week 6 (72%, 77%, 0.71, p  < .05). Anti-IFX Abs occurred in 28% of primary non-responders and associated with low IFX and treatment failure (OR 13.7 [2.8–67.5], p  < .01). Markers of disease activity (disease activity scores, albumin, CRP) also associated with low IFX. Circulating TNFα was higher throughout induction in non-responders with ulcerative colitis but not Crohn's disease. Conclusion: IBD patients with primary IFX failure generally have lower IFX trough than responders during early induction phase. Pharmacokinetic failure seems common in ulcerative colits, whereas pharmacodynamic failure appears common in Crohn's disease.